A low temperature mechanochemical synthesis of nanostructured ZrC powder by a magnesiothermic reaction. Issue 7 (August 2015) - Davoodi, Danial; Hassanzadeh-Tabrizi, S.A.; Hossein Emami, Amir; Salahshour, Saman
Abstract: Nanostructured ZrC powder was synthesized by the mechanochemical process in a high-energy ball mill by a magnesiothermic reaction. The effects of various amounts of Mg (stoichiometric and over-stoichiometric) on synthesis efficiency of the ZrC powders were investigated. The synthesized powders were studied by X-ray diffraction (XRD), differential thermal analysis (DTA), field-emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). Zirconium carbide (ZrC) was produced after 30 h milling. Thermodynamic calculation showed the reaction to be a mechanically induced self-sustaining one (MSR). DTA analysis indicated that the temperature of exothermic reaction decreases significantly after 12 h milling.